Diagnóstico de salud bucodental y factores de riesgo en los centros educativos: Fray Vicente Soliano, Juan Ullauri, Pedro López Medrano, Matilde Palacio de Jaramillo y Dr. Ricardo Sotomayor de la parroquia Rural de Yangana del Cantón Loja año, 2013. - Silva Celi, María de los Angeles (2013)
SUMMARY Dental caries and periodontal disease have been considered heavier diseases in the history of oral morbidity Worldwide , National and respect to the South, because of this reason that there is the need for a and observational study to determine the diagnostic descriptive oral health and risk factors in the population of Yangana , belonging to the canton Loja. The objective of the research is to diagnose oral health of schoolchildren Fray Vicente Solano, Juan Ullauri, Pedro López Medrano, Matilde Palace Jaramillo and Dr. Ricardo Sotomayor Year 2013. To carry out this project was identified risk factors that influence students' oral health and determined the prevalence of major diseases. This study consisted of 168 children from five schools, in which a survey was conducted and a medical history. Among the main results emerged, the 94.64 % of the population had dental caries, gingival inflammation on 52.38 %. As for the ceo- d in children 3-5 years of age have a high index of 5.97, and the CPO-D the ages of 9 and 11 years, being 3.03. So it is concluded that the risk factors associated mostly with the appearance of dental caries was uncontrolled intake of cariogenic diet, poor brushing technique and poor oral hygiene. KEY WORDS: Oral health, children, dental caries, gingival inflammation, and risk factors